Facing the Impact of Climate Change on Global Health: Science and Technology Based Adaptation - Demir, Ahmet; Erdogan, Aylin; Musdania, Musdania; Zani, Benny Novico (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Climate change poses a significant threat to global health, exacerbating existing health challenges and creating new risks. Rising temperatures, extreme weather events, and shifting disease patterns are already contributing to the increasing burden of diseases such as malaria, heatstroke, and respiratory disorders. This research explores the role of science and technology in adapting to the health impacts of climate change, focusing on innovative solutions to mitigate the health risks associated with environmental changes. The study employs a systematic review approach, analyzing data from 50 peer-reviewed studies that examine technological advancements, such as climate-resilient healthcare infrastructure, early warning systems, and the development of heat-resistant crops. The results indicate that technology-based adaptation strategies can significantly reduce the impact of climate change on public health by improving disease forecasting, enhancing healthcare system resilience, and supporting preventive measures. The study concludes that multi-disciplinary approaches involving science, technology, and policy-making are crucial to address the health challenges posed by climate change. Collaboration across sectors is needed to implement these strategies on a global scale, ensuring equitable access to climate-related health solutions. This research underscores the importance of continued investment in climate-resilient health systems to safeguard global health in the face of climate change.